FAKTOR – FAKTOR YANG MEMPENGARUHI KETEPATWAKTUAN PELAPORAN KEUANGAN DAN KEANDALAN PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Di Pemerintah Daerah Kabupaten Ogan Ilir) - Afrida, Anggrelia (Universitas Muhammadiyah Palembang, 2016)
This research was conducted in the accounting / financial administration on regional work units (SKPD) Local Government Ogan Ilir totaling 29 SKPD. SKPD each represented by three members, namely the Head of Finance, treasurer and financial reporting staff as respondents .. Results from this study that the quality of human resources, internal control of accounting, organizational commitment and application of accounting standards partially government did not significantly affect the timeliness of financial reporting yet use of information technology has an influence on the timeliness of financial reporting while the reliability of financial reporting, only the use of information technology that has no effect. Fourthly other variables actually have an influence on the reliability of financial reporting